Socialisation of Forest and Land Fire Prevention on Mangrove Management Group in Buruk Bakul Village, Bengkalis Regency - Sinaga, Hafiz Hazalin; Utami, Rizka; Budijono, Budijono; Fauzi, Muhammad (Unri Conference Series: Community Engagement, 2024)
Forest and land fires in general have negative environmental, economic and social impacts. Fires not only threaten air quality and human health, but threaten the economic value of mangrove ecosystems on the coast. The socialisation of forest and land fire prevention to mangrove management groups in Buruk Bakul Village aims to provide knowledge to mangrove management groups about the role and involvement of the community in preventing forest and land fires in mangrove forest conservation activities. This socialisation is expected to make people aware of how important it is to preserve the environment and create a balance in the mangrove ecosystem. The target group of this education is the Mangrove Conservation Activist Community Group ‘Sekat Bakau’ which is one of the self-help groups in Buruk Bakul Village, Bukit Batu District, Bengkalis Regency. The method used was socialisation and tutorial on community-based forest and land fire prevention. The socialisation began with a pre-test, presentation of material accompanied by interactive discussion and post-test. At the end of the activity, a field visit was conducted to monitor fire-prone areas. The result was that the socialisation was very interactive and received a positive response from the target group who conserve and utilise mangrove areas through activities, including the Mangrove Bank, mangrove seedling planting, rehabilitation and restoration and as a mangrove educational tourism village. However, this group does not regularly receive knowledge about forest and land fires as a form of prevention. The post-activity evaluation has proven that this educational activity has increased the understanding and knowledge of the target group and for the sustainability process, it is necessary to coordinate with stake holders to make a schedule for regular and integrated socialisation of forest and land fires.